Employee Engagement Mediates Self-Efficacy and Perceived Organizational Support on Nurses’ Organizational Citizenship Behavior - Sulaimiah; Sarifudiin Serif; Harmi Widiana; Zira Wahyu (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Human resources are vital to organizational success, especially in healthcare, where psychological and organizational factors influence service quality. This study examines how self-efficacy and perceived organizational support affect organizational citizenship behavior through employee engagement among nurses at health centers. The study aims to determine whether engagement mediates the relationship between self-efficacy, perceived organizational support, and organizational citizenship behavior. Using a quantitative causal associative design, data were collected from 89 nurses and analyzed through validity and reliability tests, classical assumption tests, and path analysis, with t-tests and Sobel tests to assess direct and indirect effects. Results show that self-efficacy and perceived organizational support significantly enhance employee engagement and organizational citizenship behavior, while engagement mediates both relationships. The findings confirm the role of engagement as a psychological bridge connecting self-efficacy and organizational support to positive extra-role behavior. Health institutions should improve nurses’ self-efficacy through training, mentoring, and recognition programs while maintaining strong organizational support to foster engagement and encourage cooperative, high-quality service behavior.